2019
DOI: 10.1002/hbm.24524
|View full text |Cite
|
Sign up to set email alerts
|

Generalizing age effects on brain structure and cognition: A two‐study comparison approach

Abstract: Normal aging is accompanied by an interindividually variable decline in cognitive abilities and brain structure. This variability, in combination with methodical differences and differences in sample characteristics across studies, pose a major challenge for generalizability of results from different studies. Therefore, the current study aimed at cross‐validating age‐related differences in cognitive abilities and brain structure (measured using cortical thickness [CT]) in two large independent samples, each co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 92 publications
(137 reference statements)
3
20
1
Order By: Relevance
“…In our study, harmonization was limited to the post-processing of DTI maps pre-computed by each site using the same script for generating individual skeletons and computing individual DTI parameter values across these skeletons. However, our findings indicate that it is possible to draw meaningful conclusions from such minimal harmonization by focusing on the effects of interest (age in our case) rather than the absolute values of the measurements, an approach previously used by others (37).…”
Section: Methodsological Issues and Potential Limitations Of The Presementioning
confidence: 81%
“…In our study, harmonization was limited to the post-processing of DTI maps pre-computed by each site using the same script for generating individual skeletons and computing individual DTI parameter values across these skeletons. However, our findings indicate that it is possible to draw meaningful conclusions from such minimal harmonization by focusing on the effects of interest (age in our case) rather than the absolute values of the measurements, an approach previously used by others (37).…”
Section: Methodsological Issues and Potential Limitations Of The Presementioning
confidence: 81%
“…Since longitudinal studies are time and resource-intensive, a fruitful solution to increase sample size is to pool data across multiple sites. An advantage of data pooling is that it allows researchers to test the replicability of their results in a different sample, and thus gain more insights into the generalizability of their findings (Jockwitz et al, 2019). While the present study is one of the first to include four repeated measurements of both neuroimaging and cognitive data, studies with more follow-ups and different time intervals are needed to explore the temporal dynamics of age-related changes in the brain, and their impact on subsequent changes in cognitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that brain function or connectivity is decreased in posterior regions and increased in anterior regions in aging (Davis et al, 2008;Jockwitz et al, 2019;Ren et al, 2019). This phenomenon is defined as the Posterior-Anterior Shift in Aging (PASA) (Davis et al, 2008).…”
Section: Differences Between Younger and Older Adults In The Neural Cmentioning
confidence: 99%